Strategic Management Education In Improving Competitiveness The Pondok Pesantren "Al Amin " Mojokerto - Wahib, Abd. (International Journal of Educational Research & Social Sciences, 2023)
The aim of this research is to determine the strategic management of education in increasing competitiveness at the Al-Amin Mojokerto Islamic boarding school. The research method used is a qualitative research approach.The data collection procedure used in this research is: Participant Observation. in-depth interviews (in deep interviews), and Documentation. This research uses a case study design, so analyzing the data is carried out in three stages, namely: (1) data condensation, (2) data presentation, and (3) verification and drawing conclusions. Research results regardingstrategic management in increasing competitiveness at the Al Amin Mojokerto Islamic boarding school, namely: 1) The condition of demand for Islamic boarding schools with an increase in students every year, demand is getting bigger every year, Good management by providing Islamic boarding schools, Good communication with the head and foundation for the advancement of madrasas, adding educational staff and infrastructure, 2) Offers made by Islamic boarding schools by preparing and managing students well, students must board, so that students can go to school and recite the Koran, creating a clean and healthy environment, integrating the Ministry of Religion's curriculum learning and Salafiyah curriculum. 3) Marketing carried out by Islamic boarding schools is as follows: a) by combining learning from the Ministry of Religion curriculum and the Salafiyah curriculum, and supporting the development of life skills and achievements by providing qiro'atul Qur'an training, monthly khitobah, computer courses, bahtsul masail, tahfidz al-Qur'an, coaching and achievement development programs for subjects and special programs. b) the costs allocated are in accordance with the budget, economical and in accordance with needs and simplicity, c) by utilizing alumni because alumni are real living brochures and through websites and marching competitions. d) Location of the Islamic boarding school, namely: access to the madrasa is very easy and there is expansion of the location. b) the costs allocated are in accordance with the budget, economical and in accordance with needs and simplicity, c) by utilizing alumni because alumni are real living brochures and through websites and marching competitions. d) Location of the Islamic boarding school, namely: access to the madrasa is very easy and there is expansion of the location. b) the costs allocated are in accordance with the budget, economical and in accordance with needs and simplicity, c) by utilizing alumni because alumni are real living brochures and through websites and marching competitions. d) Location of the Islamic boarding school, namely: access to the madrasa is very easy and there is expansion of the location.